2017
DOI: 10.1080/19393210.2017.1315743
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide residues in orange fruit from citrus orchards in Nuevo Leon State, Mexico

Abstract: Some international organisations established maximum residue limits (MRLs) in food to protect human health. Mexico lacks regulations in this matter, affecting national and international trade from agroindustry. The aim of this study was to diagnose pesticide residues in oranges from Nuevo Leon, México, in citrus orchards. In May 2014, 100 orange fruit samples were taken randomly from orchards and subjected to analysis for 93 pesticides at residual level by GC/QQQ-MS and LCQ-TOF-MS. Results showed the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Temperature, moisture, rain, sunlight, and biota are the main parameters responsible for pesticide dissipation and they change from one region to another [11]. Many studies have reported the presence of imidacloprid [13,14], pyraclostrobin [15], and difenoconazole in oranges [16]. It is clearly established that the dissipation behavior of these compounds under field conditions depends on diverse factors, including plant species, chemical formulation, application method, weather conditions, and crop growth characteristics [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature, moisture, rain, sunlight, and biota are the main parameters responsible for pesticide dissipation and they change from one region to another [11]. Many studies have reported the presence of imidacloprid [13,14], pyraclostrobin [15], and difenoconazole in oranges [16]. It is clearly established that the dissipation behavior of these compounds under field conditions depends on diverse factors, including plant species, chemical formulation, application method, weather conditions, and crop growth characteristics [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mac Loughlin et al found that in the 135 samples of fruits and vegetables in Argentina markets, the largest residual pesticide content was detected in oranges—30% of the tested oranges exceeded MRLs [ 19 ]. In 11% of the tested orange samples in Mexico, the concentrations of methyl chlorpyrifos, malathion, and methidathion were all over the MRLs of the European Union [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…As with the current study, pesticide residues in 30% of the orange samples in the Argentine domestic market were found to be > MRL ( Mac Loughlin et al., 2018 ). Suárez-Jacobo et al. (2017) found that a total of 11% orange samples in Mexico exceeded the EU MRL including dimethoate (1%), malathion (5%), chlorpyrifos-ethyl (1%), and methidathion (4%).…”
Section: Resultsmentioning
confidence: 99%